2019
DOI: 10.1038/s41563-019-0371-y
|View full text |Cite|
|
Sign up to set email alerts
|

A mechano-signalling network linking microtubules, myosin IIA filaments and integrin-based adhesions

Abstract: A mechano-signalling network linking microtubules, myosin IIA filaments and integrin-based adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(165 citation statements)
references
References 55 publications
9
152
4
Order By: Relevance
“…The increased sensitivity of MDA-MB-435S cells to both MT poisons upon integrin αV or KANK2 knockdown points to altered MT dynamics in these cells. Consistently, recent data in other cell models have shown that KANK proteins mediate crosstalk between actin and MT cytoskeletons at FAs (Bouchet et al, 2016;Sun et al, 2016;Chen et al, 2018;Rafiq et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…The increased sensitivity of MDA-MB-435S cells to both MT poisons upon integrin αV or KANK2 knockdown points to altered MT dynamics in these cells. Consistently, recent data in other cell models have shown that KANK proteins mediate crosstalk between actin and MT cytoskeletons at FAs (Bouchet et al, 2016;Sun et al, 2016;Chen et al, 2018;Rafiq et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…KANK1 has an essential role in cytoskeleton maintenance via regulating the rate of cytoskeleton proteins production and controlling actin polymerisation [4]. KANK1 plays an important role in the down-regulation of the Rho-associated kinase (ROCK) pathway [5], which is recognised to be involved in various cellular functions such as proliferation, adhesion, cell differentiations and apoptosis [6]. This allow KANK1 to integrate alongside with β-catenin aiming to regulate its distribution in the nucleus and concentrate its transcription, therefore, affecting the development of cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the four KANK proteins, KANK1-KANK4, have been described as 'seeds' that initiate the formation of a cortical platform assembly for the stabilisation of microtubules (Bouchet et al, 2016;Sun et al, 2016). KANK1 and KANK2 localise around FAs and podosomes (Rafiq et al, 2019). KANK1 links the CMSC to FAs through its direct interaction with both talin and liprin-β1 (Bouchet et al, 2016;Sun et al, 2016).…”
Section: Recruitment Of Cortical Partners Near Fasmentioning
confidence: 99%
“…How the GEF-H1 interaction with microtubules is regulated is still a matter of debate. Uncoupling microtubules from FAs, by depleting KANKs, releases GEF-H1 from microtubules (Rafiq et al, 2019), which indicates that anchoring microtubules at FAs inhibits GEF-H1 and may act as a negative-feedback loop to prevent excessive acto-myosin-mediated forces at FAs. Signalling cascades involving the serine threonine kinase Par1b/MARK2, as well as p21-activated-kinase 4 (PAK4), phosphorylate GEF-H1, which promotes its release from microtubules (Callow et al, 2005;Yoshimura and Miki, 2011).…”
Section: Meddling With the Fa-actin Duomentioning
confidence: 99%